(untitled) - Trần, Minh Thành (Cần Thơ, 1995)
The following list contains books in the field of agriculture, to be purchased for the CTUL. Baisc for the selection was a search for books in the field of Agriculture on the BookFind CD-ROM, resulting in approximately 2500 available titles. A list of the titles produced from this database circu;aed among the agricultural faculties.
Keywords: Agricultural bibliography